Pembuatan Lilin Aromaterapi dari Limbah Minyak Jelantah sebagai Upaya Pemberdayaan Ibu-Ibu PKK di Desa Kejagan - Widya Nur Rachmawati; Estevania Angel Gloria; Lu'lu'ul Mukarromah; Vanesa Rosavia Berlina; Gusti Nathan Pangestu; Anisa Mamba’ul Fitri; Derri Ardi; Citra Pramita Hermayanti; Siti Ismidul Uyun; Arianto Nara Rizky Ramadhan; Yanda Bara Kusuma (Nusantara Mengabdi Kepada Negeri, 2024)
This Real Work Lecture (KKN) activity was carried out to empower Family Welfare Empowerment (PKK) mothers in Kejagan Village through training in making aromatherapy candles made from used cooking oil. The aim of this activity is to increase the knowledge and skills of PKK women in utilizing used cooking oil into economically valuable products, as well as providing an alternative home business that can increase family income. The method used was a demonstration, where the KKN team demonstrated the process of making aromatherapy candles from used cooking oil directly to the participants. The material provided includes an introduction to used cooking oil, making candles, adding coloring, and using essential oils as fragrances. After the training, participants are given the opportunity to practice making aromatherapy candles independently. Evaluation of activities shows that there has been an increase in the knowledge and skills of PKK women in utilizing used cooking oil into products of marketable value. Apart from that, participants were also enthusiastic about developing an aromatherapy candle business as a home business opportunity. This KKN activity can be a model for community empowerment based on local potential that can be applied in other villages.